Analisa Faktor yang Mempengaruhi Kondisi Kesehatan Menggunakan Algoritma Frequent Pattern Growth - Sukma Evadini; Alwis Nazir; Yusra Pizaini (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2018)
Health is an important factor in human life that have to be guarded, both physically and mentally. This study aimed to analyze the factors that affect health condition using medical check up data. Factors analyzed were consuming alcohol, smoking, exercise, age and gender. The method was the association rule using FPGrowth. The result of this study was factors that affect the health condition is alcohol, exercise and age. This result evidenced by the rules A3→K3, which means that if a person consumes more alcohol than 4 days/week with the amount of alcohol is less than 180ml/day, then health condition was poor with 11% support and 67% confidence. E1→K3, which means that if one rarely exercise then health condition was poor with 24% support and 99% confidence. G2→K3, which means that if a person in middle age group, then the condition of health was poor with 24% support and 99% confidence.